Experiences of intervention of social workers with male sex workers in Bogotá, Colombia - Barrera-Castellanos, Johan Arturo (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This article presents an account of the experience of five female social workers in intervention processes with male sex workers in Bogotá, Colombia, as part of their work with both State and civil institutions. A qualitative approach framed under the postulates of social constructionism was adopted, which is why, a semi-structured interview was chosen as the instrument for gathering information. A lack of theoretical and methodological guidelines that acknowledge male sex workers becomes apparent and this leads to a feminization of the assistance given to them, justified, in turn, by reductionist precepts that set up a biased research logic. This logic is apparent in the professional practice and the institutional vision, both in State and civil institutions. Consequently, some challenges for social workers’ addressing of male individuals who engage in the sex trade are laid out based on the evidence collected and under the understanding of the sex trade as a complex social phenomenon.